New-Onset Nephrotic Syndrome in a Child Associated With COVID-19 Infection - Shah, Siddharth A.; Carter, Helen P. (Frontiers in Pediatrics, 2020)
Introduction: The COVID-19 outbreak has become a worldwide public health emergency. The renal histopathological features of acute tubular necrosis or thrombotic microangiopathy have been previously reported in adults with severe COVID-19 infections. In children, the renal manifestations associated with COVID-19 disease are not widely reported. Here we describe a case report of a child with new-onset nephrotic syndrome associated with COVID-19 infection. Case Presentation: An 8-year-old boy with no previous significant medical history presented with bilateral eyelid and facial swelling soon after his parents were diagnosed with COVID-19 infection. He had diarrhea but no fever or shortness of breath. At 1 week after the onset of swelling, the boy tested positive for the COVID-19 virus. Based on clinical findings of significant proteinuria (urine protein and creatinine ratio of 11.4), hypoalbuminemia (serum albumin of 2 g/dl), and hypercholesterolemia (total cholesterol of 384 mg/dl), he was diagnosed with nephrotic syndrome. He responded well to standard-dose prednisone treatment for nephrotic syndrome. At 1 week after starting the prednisone treatment, he went into clinical remission. Lymphopenia continued to be present for 4 weeks after the onset of symptoms. There were no complications related to clot formation or secondary infections with this presentation. Conclusion: COVID-19 can be associated with new-onset nephrotic syndrome in children. The patient responded well to the standard-dose prednisone treatment that is typically used for new-onset nephrotic syndrome. Summary: We describe the unique presentation of COVID-19 in a child as new-onset nephrotic syndrome. We offer insight on the success of standard treatment of nephrotic syndrome with COVID-19.